Pathophysiological Mechanisms and Potential Therapeutic Targets in Intracerebral Hemorrhage - Shao, Zhiwei; Tu, Sheng; Shao, Anwen (Frontiers in Pharmacology, 2019)
Intracerebral hemorrhage (ICH) is a subtype of hemorrhagic stroke with high mortality and morbidity. The resulting hematoma within brain parenchyma induces a series of adverse events causing primary and secondary brain injury. The mechanism of injury after ICH is very complicated and has not yet been illuminated. This review discusses some key pathophysiology mechanisms in ICH such as oxidative stress (OS), inflammation, iron toxicity and thrombin formation. The corresponding therapeutic targets and therapeutic strategies are also reviewed.